Ecological models and business practices - Díaz-Villavicencio, G. (2017)
The following paper shows the state of the art in the measurement of eco-efficiency, in doing so, taking the ecological context as a foundation of inspiration within the environmental sciences as a joint interdisciplinary. From this premise we are able to observe that environmental policies have a point of connection at the time in which beliefs of ecologists are in tow with the actions with which the corporate world promotes. It becomes possible to see that it forms a concept (Eco-DEA) which presents itself as a tool that gives support to different types of corporate actions so as to maintain industrial production levels whilst simultaneously caring for the environment.